Reconstrucción post-tsunami y proceso de paz en ACEH: dos agendas y un destino - Lechiguero Pardo, Luis (Revista Española de Desarrollo y Cooperación, 2023)
An important effect of the tsunami in Aceh (Indonesia) was the sparking off the peace process between the independent movement GAM and the Government of Indonesia, eight months after the disaster. The present article identifies some of these connexions between both processes, post-disaster and post-conflict, and presents some of the dilemmas and paradoxes founded at the field level.